1983
DOI: 10.1073/pnas.80.11.3485
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth of a prolactin-secreting pituitary tumor in rats by analogs of luteinizing hormone-releasing hormone and somatostatin.

Abstract: We investigated the effects of [D-Trp6]LH-RH [agonistic analog of luteinizing hormone-releasing hormone (LH-RH)], N-Ac-[D-p-Cl-Phe1,2,D-Trp3,D-Phe6,D-Ala10]LH-RH (antagonistic analog), and [D-5-methoxy-Trp8]somatostatin (somatostatin analog) on the growth of the prolactin and corticotropin-secreting pituitary tumor 7315a in female Buffalo rats. Chronic administration of [D-Trp6]LH-RH in a dose of 25 micrograms/day, starting 18 days after inoculation with the tumor, inhibited the growth of the pituitary tumor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…An antimitogenic factor of natural origin might find a possible application in the treatment of some neoplasias, and it could provide an alternative to chemotherapeutic agents, most of which have deleterious effects. Further work might show whether, in addition to the recently developed treatment of endocrine-dependent tumors with synthetic analogs of hypothalamic hormones (15)(16)(17)(18)(19), another approach based on this naturally occurring hypothalamic substance would prove feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An antimitogenic factor of natural origin might find a possible application in the treatment of some neoplasias, and it could provide an alternative to chemotherapeutic agents, most of which have deleterious effects. Further work might show whether, in addition to the recently developed treatment of endocrine-dependent tumors with synthetic analogs of hypothalamic hormones (15)(16)(17)(18)(19), another approach based on this naturally occurring hypothalamic substance would prove feasible.…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated suppressive effects of luteinizing hormone-releasing hormone analogs and somatostatin analogs on pituitary tumors (18) and on chondrosarcomas in rats (19). Continuing our investigations on the effects of hypothalamic substances on cancer, we decided to examine the influence of partially purified fractions of porcine hypothalami on cell proliferation in tissue cultures.…”
mentioning
confidence: 99%
“…Inhibition of the growth of endocrine-dependent mammary, prostate, and pituitary tumors by analogs of hypothalamic hormones has recently been demonstrated (22)(23)(24) In the second experiment with hamsters bearing the ductal pancreatic adenocarcinoma ( (5)(6)(7). Although secretin is not as potent as CCK, it also increases pancreatic weight, DNA, RNA, and protein content (7).…”
mentioning
confidence: 99%
“…This highly active agonistic analog of LH-RH has been shown to exert paradoxical inhibitory effects on the pituitary-gonadal axis in both animals and human beings when given chronically (2,3). This inhibition of reproductive functions produced by chronic administration of LH-RH and other LH-RH agonists has been utilized to induce a regression of various hormone-sensitive neoplasms such as mammary carcinomas, prostate tumors, and pituitary tumors (4)(5)(6)(7). It has been shown that long-te~rm administration of agonistic and antagonistic analogs of LH-RH inhibited the growth of the 7315a transplantable rat pituitary tumor, which secretes both prolactin (PRL) and corticotropin (ACTH) (6,7).…”
mentioning
confidence: 99%
“…This inhibition of reproductive functions produced by chronic administration of LH-RH and other LH-RH agonists has been utilized to induce a regression of various hormone-sensitive neoplasms such as mammary carcinomas, prostate tumors, and pituitary tumors (4)(5)(6)(7). It has been shown that long-te~rm administration of agonistic and antagonistic analogs of LH-RH inhibited the growth of the 7315a transplantable rat pituitary tumor, which secretes both prolactin (PRL) and corticotropin (ACTH) (6,7). In order to study further the inhibitory effect of [D-Trp6]LH-RH on pituitary tumors, we decided to extend our investigations to the PRL-and growth hormone (GH)-producing GH3 rat pituitary tumor.…”
mentioning
confidence: 99%